Influence of Amorphous, Carbon‐Derived Wrinkled Surface Topologies on the Colonization of Pseudomonas aeruginosa Bacteria. Issue 7 (19th February 2019) - Nguyen, Duy H. K.; Wang, James; Sbarski, Igor; Juodkazis, Saulius; Crawford, Russell J.; Ivanova, Elena P.
Abstract: Surface wrinkling is a natural phenomenon that has inspired an emerging technology in surface patterning. Here, it is demonstrated that thermal treatment planar thin films of amorphous graphite‐like carbon (G‐aC) coatings deposited on shape memory polystyrene could be used to prepare substratum surfaces with topologies ranging from smooth undulations to those with rough distortion features. A comparative analysis of the attachment propensity of Pseudomonas aeruginosa ATCC 9721 and alginate‐overproducing P. aeruginosa PW2390 bacterial cells, together with the associated production of extracellular polymeric substances (EPS), reveal that at least a 13‐fold increase in the cell attachment density could be achieved, reaching up to 1.3 × 10 5 and 1.8 × 10 5 cells mm −2 being attached to the surface for both bacterial strains on G‐aC wrinkled surfaces. The P. aeruginosa PW2390 cells attached to a greater extent than the P. aeruginosa ATCC 9721 cells (≈45%) and without any increased production of EPS material. It is suggested that the increased level of cell attachment is related to the associated substantial increase in available substratum surface area. The results of this study afford a useful insight toward the production of substrata using a straightforward, tunable, and low cost microfabrication approach. Abstract : A straightforward fabrication approach of wrinkled amorphous graphite‐like carbon (G‐aC) coatings on polystyrene substrata is developed by taking advantage of the buckling, buckling‐driven delamination, and cracking at unstable G‐aC/polystyrene interface. This work provides a better understanding of the role of extracellular polymeric substances and wrinkled topographies in the design of an efficient antifouling substratum.